VILLAGE GOVERNMENT POLICIES IN EFFORTS TO PRESERVE MAPPADENDANG HARVEST PARTY IN BINUANG VILLAGE, BALUSU DISTRICT, BARRU DISTRICT - Asriani; M, A. Pananrangi; Patonangi, Andi Maulana (P3M Stia Al Gazali Barru and Meraja media, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal